Analisis Faktor-Faktor yang Memengaruhi Peningkatan Produksi Susu di Kecamatan Pujon Kabupaten Malang Jawa Timur - Soeyatno, Rahmah Farahdita; Sucayono, Sucayono (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The national dairy cattle industry from 2005 to 2011 experienced low productivity and fluctuating production. Over 90% of the business is dominated by small-scale, traditional farms, which are generally inefficient. Farmers face significant limitations in production capacity, management, and technological maintenance. These challenges directly impact their income, which is influenced by resource costs and business operations. Pujon Sub-district in East Java, a major dairy production center, has the potential to improve farmers’ welfare through enhanced dairy income. This study aims to analyze the factors influencing milk production among dairy farmers. A quantitative approach was used, employing multiple linear regression analysis based on the Cobb-Douglas production function. Research was conducted in Pandesari Village, Pujon Sub-district, Malang, from September 2012 to January 2013. A total of 36 farmers and 103 dairy cows were surveyed using purposive sampling. Data collection methods included interviews, observations, questionnaires, and literature reviews. Variables analyzed were feed, lactation, artificial insemination, labor, and training. The results showed that farm management was generally effective. The model estimated an R² value of 86.5%, indicating that feed concentrate, forage, labor, and cassava waste significantly influenced milk production, under constant returns to scale. The SAE Pujon Cooperative is encouraged to enhance farmer training to improve milk quality.